KAJIAN YURIDIS PASAL 23 AYAT 1 UNDANG-UNDANG NOMOR 2 TAHUN 2011 TENTANG PARTAI POLITIK MENGENAI BATAS MASA JABATAN KETUA PARTAI POLITIK - Hendra Tri Ferdianto; Icha Cahyaning Fitri (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study addresses the urgency of limiting the tenure of party leaders in Indonesia to strengthen the democratic system. According to Karl Popper, democracy allows citizens to control their leaders, contrasting with authoritarian leadership styles. Indonesia, as a democratic nation, recognizes the crucial role of political parties in political dynamics, regulated under Law No. 2 of 2011. However, this law does not specifically address the tenure limits of party leaders, leading to potential abuse of power and the emergence of political dynasties. This research highlights cases such as PDIP, Demokrat, and Gerindra, where party leaders have held their positions for extended periods. The study advocates for the implementation of standardized rules regarding the term limits of party leaders to prevent authoritarianism and ensure a healthy democracy.